Action research as a method to increase knowledge and communication in a sports performance setting - Höök, M.; Knight, C.; McGawley, K. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Athletes may suffer from mental illnesses, eating disorders, low energy availability and/or hormonal symptoms 1-3, all of which negatively affect health and performance. Knowledge about these issues is limited among coaches and athletes, which makes attempts to solve problems difficult. Education is recommended to increase the willingness of athletes and coaches to communicate about sensitive or "taboo" topics4, but information about how best to educate these individuals is limited. The overall aim of this project was to develop, implement and evaluate a programme of education using an action research approach 5. This paper critically discusses the application of action research when seeking to develop such education programmes.